The effect of 12-week outward-bound training on sports attitude, heart rate and physical fitness among college students in China - Gao, Jianxin; Abdullah, Borhannudin; Dev, Roxana Dev Omar (Nevzat Demirci, 2024)
Outward-bound training (OBT) originated in the UK as an outdoor survival method during World War II and is an experiential training course that emphasizes shaping teamwork, enhancing and strengthening individual psychological and athletic potential, and promoting organizational growth. However, OBT to improve sports attitude and physical fitness among college students remains unclear. The purpose of this study investigated the effect on sport attitude, heart rate and physical fitness among college students in China. Sixty college students (Aged 18-20, 19.05±0.85y) who were selected from Jiangxi Teachers College took part in this study. Participants were randomly assigned into two groups EG and CG. The EG completed 12 weeks OBT combined normal PE class intervention and the CG only for 12 weeks normal PE class intervention. The result indicated that the EG was statistically significant difference than control group after Paired-samples T test analysis for sports attitude questionnaire score (Male T=-11.515, P=0.001 and Female T=-23.070, P=0.001); HRMax (Male T=-5.755, P=0.001 and Female T=-4.007, P=0.001); HRAvg (Male T=-5.072, P=0.001 and Female T=-4.801, P=0.001); 50m run (Male T=8.085, P=0.001 and Female T=8.413, P=0.001); 800m run (Female T=5.949, P=0.001); 1000m run (Male T=3.722, P=0.001); Standing long jump (Male T=-2.233, P=0.042 and Female T=-5.824, P=0.001); Sit and reach (Male T=-3.872, P=0.002 and Female T=-5.274, P=0.001); Sit-up (Female T=-11.042, P=0.001); Pull-up (Male T=-4.276, P=0.001). Therefore, the conclusion suggested that 12-week OBT intervention was significant to improve sports attitude, heart rate and physical fitness among college students in China.